Enfrentamento à violência doméstica : uma causa comum aos movimentos de mulheres - Santos, Verônica de Barros (2022)
Confronting domestic violence is an agenda present in the claims of women's movements and in government agendas. It is an internationally constructed public problem, incorporated into national government programs and converted into a public policy issue. The trajectory of the problem is marked by the activism of women in supranational spaces, in state bureaucracy and in different forms of collective association. Despite the historical claims of women's movements being composed of an extensive list of agendas, domestic violence stands out as a point of convergence for social movements and political groups of different tendencies, unlike the agendas related to sexual and reproductive rights. The objective of this research is to understand the construction of domestic violence as a common agenda for women's movements, becoming a highly visible social cause and one of the main issues of policies for women in Brazil. To apprehend the social conditions of evidence of this agenda, we carried out the sociogenesis of the public cause, analyzed the policies for women of the Brazilian government, reflected on the performance of engaged professionals and debated about changes in coping policies, as a reflection of changes in the political scenario. national. Thus, the fight against domestic violence is an international, diversified and specialized cause that mobilizes different affections and different actors/actresses and that is consolidated with the presence of women in the state bureaucracy. From the trajectory of the cause, we conclude that the fight against domestic violence is a femocratic cause, built by women in institutional spaces and consolidated in bureaucratic spaces, making it an issue easily framed in different perspectives and social and political contexts.